Paper-Based Analytical Devices Based on Amino-MOFs (MIL-125, UiO-66, and MIL-101) as Platforms towards Fluorescence Biodetection Applications - Piguillem Palacios, Sofía Viviana (2024)
In this study, we designed three promising platforms based on metal–organic frameworks(MOFs) to develop paper-based analytical devices (PADs) for biosensing applications. PADs havebecome increasingly popular in field sensing in recent years due to their portability, low cost, simplicity,efficiency, fast detection capability, excellent sensitivity, and selectivity. In addition, MOFsare excellent choices for developing highly sensitive and selective sensors due their versatility forfunctionalizing, structural stability, and capability to adsorb and desorb specific molecules by reversibleinteractions. These materials also offer the possibility to modify their structure and properties,making them highly versatile and adaptable to different environments and sensing needs. In thisresearch, we synthesized and characterized three different amino-functionalized MOFs: UiO-66-NH2 (Zr), MIL-125-NH2 (Ti), and MIL-101-NH2 (Fe). These MOFs were used to fabricate PADscapable of sensitive and portable monitoring of alkaline phosphatase (ALP) enzyme activity bylaser-induced fluorescence (LIF). Overall, amino-derivated MOF platforms demonstrate significantpotential for integration into biosensor PADs, offering key properties that enhance their performanceand applicability in analytical chemistry and diagnostics.